2014
DOI: 10.1002/mus.24061
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of panoramic ultrasound imaging to simultaneously examine muscle size and quality of the medial gastrocnemius

Abstract: These results suggest that panoramic US imaging may be a reliable technique for simultaneous assessment of both muscle size and quality from a single US scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 43 publications
7
91
2
2
Order By: Relevance
“…Connective tissue and lipid are more reflective than more dense muscle tissue and are depicted in the image as lighter gray [142]. Ultrasound has been shown to be a reliable tool for assessing muscle quality as echo intensity [143,144] (a proxy of muscle composition), which may be considered an index of muscle quality. Analyzing the reflectivity via gray-scale analysis provides a useful low-cost, easily accessible, and safe method to evaluate the muscle quality [145].…”
Section: Skeletal Muscle Ultrasoundmentioning
confidence: 99%
“…Connective tissue and lipid are more reflective than more dense muscle tissue and are depicted in the image as lighter gray [142]. Ultrasound has been shown to be a reliable tool for assessing muscle quality as echo intensity [143,144] (a proxy of muscle composition), which may be considered an index of muscle quality. Analyzing the reflectivity via gray-scale analysis provides a useful low-cost, easily accessible, and safe method to evaluate the muscle quality [145].…”
Section: Skeletal Muscle Ultrasoundmentioning
confidence: 99%
“…This results in a histogram of grayscale shades (0: black, 256: white), where any abnormalities-such as edema-induced muscle swelling, probably due to muscle damage-result in higher US echo value (high echogenicity-increased white areas), while normal muscle mass has low echogenicity (less white areas). This method has been used extensively in the evaluation of exercise-induced changes in muscle quality and is indicative of edema and damage (Rosenberg et al 2014;Chen et al 2009Chen et al , 2012Chen et al , 2013Nosaka and Sakamoto 2001;Chen and Nosaka 2006;Gonzalez-Izal et al 2014). The same experienced investigator collected all images and conducted all analyses, which took place in a blinded manner.…”
Section: Muscle Cross-sectional Area (Csa) and Csa Echo Intensity (Csmentioning
confidence: 99%
“…For example, Cadore et al (2014) recently reported that increases in maximal torque production after 6 wk of isokinetic training were significantly related to improvements in EI, which suggests that training-induced increases in muscle quality are linked to improvements in maximal strength. In light of these findings and given the potential contribution of CSA, MT and EI to measures of maximal and explosive strength and other functionally important parameters, recent research studies have heavily focused on identifying highly sensitive and reliable non-invasive imaging techniques for assessing muscle size and quality measurements (Caresio et al 2014;Melvin et al 2014;Rosenberg et al 2014;Strandberg et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although MRI and CT have been reported to be reliable and effective devices for examining muscle size and quality (Housh et al 1995;Strandberg et al 2010), these imaging technologies are expensive, time consuming and inaccessible to most researchers and clinicians (Ahtiainen et al 2010;Rosenberg et al 2014). The need for a more cost-effective and readily accessible technique to quantify muscle size and quality in both laboratory and clinical settings has been suggested by previous studies that have used brightnessmode (B-mode) ultrasound (US) imaging devices during various muscle assessments of the upper and lower extremities (Arts et al 2010;Caresio et al 2014).…”
Section: Introductionmentioning
confidence: 99%